Radical Retinoscopy in the Low Vision Examination: A Case Report - Strong, J Graham (Canadian Journal of Optometry, 1982)
The case of a 31 year old low vision patient is reported. A review of her ocular status is made in this presentation. Although conventional retinoscopy is impossible, radical retinoscopy provides a reasonably accurate refraction. Spectacle correction of this hitherto undetected refraction provides the basis for successful low vision therapy.